MR magnetization transfer measurements in temporal lobe epilepsy: a preliminary study. - Tofts, P S; Sisodiya, S; Barker, G J; Webb, S; MacManus, D; Fish, F; Shorvon, S (American Journal of Neuroradiology, 1995)
MR magnetization transfer ratio was measured in both hippocampi of three patients with temporal lobe epilepsy, and in two control subjects. The magnetization transfer ratio in each section was significantly lower on the affected side than on the contralateral side and in control subjects. Magnetization transfer ratio measurements are relatively fast and precise, this preliminary study shows that they may provide useful presurgical information.